A Sociological Exploration of Road Accessibility and its Influence on People’s Livelihood - Pandey, Bachu Kailash; Pathak, Jagat Raj (NPRC Journal of Multidisciplinary Research, 2025)
This paper tries to exploration of the road accessibility and its influence on people’s livelihood. The primary objective of this study was to assess the impact of road accessibility on the livelihoods of rural residents in Gothikada village, located in Birendranagar Municipality-14, Surkhet. Fieldwork methods, including direct observation, interviews, and case study, were utilized to gather data. The findings reveal that Gothikada lacked essential social services, requiring residents to travel to Birendranagar Bazaar for access. Prior to the enhancement of road infrastructure, villagers faced substantial hardship due to limited access to these services. However, following road improvements, residents gained easier access to services in nearby areas, positively influencing their quality of life. The study further documents both positive and negative effects of improved road accessibility on the villagers, examining shifts in their daily livelihood activities and the broader relationship between infrastructure development and socio-economic conditions. The research highlights the transformative role of road accessibility in shaping rural livelihoods and community dynamics of the study area.